98.0k views
5 votes
The Pythagorean theorem is a² + b² = c². Solve for b. b=±c+a−−−−√ b=±c2−a2−−−−−−√ b=±c2+a2−−−−−−√ b=±c−a−−−−√

User Jstrong
by
5.7k points

2 Answers

0 votes

Answer:

B. b = +- sqrt (c^2 - a^2)

Explanation:

I just took the test!!!

User Jeremy Giberson
by
5.8k points
5 votes


a^(2) +b^(2) =c^(2)

As we have to solve for b, it means we have to isolate b

So first of all subtract
a^(2) from both sides

So we get


b^(2) =c^(2) -a^(2)

Now we need b , but its b^2 , so we can take square root on both sides.


taking square roots on both sides


b= +- √(c^2 -a^2)


Hence option B is correct

User Martin Cassidy
by
5.7k points